The Influence of Teacher Professional Competence on Student Learning Motivation in PAI Subjects - Arrobi, Jimatul; Supiani, Endang; Lestari, Sri Rahayu (Al-Hijr: Journal of Adulearn World, 2023)
A successful teacher is a teacher who has competence so that it can increase the enthusiasm and motivation of learning of students, and ultimately will improve the quality of learning felt by students. Teacher competence is very important. We can see from the interest of students in the learning process. For example, such as always doing assignments given by the teacher, not being late in participating in learning, but what the author sees from the research results there are still students who are less focused when learning, lack interest in learning in certain subjects, and there are still students who don't do assignments . It means that the liveliness expected of a teacher in the teaching and learning process is not as expected by the teacher. This research was conducted at SMA Negeri 3 Kota Sukabumi in class XII IPS with a total of 167 students. The sample that the researcher took was 25 students, 15% of the total population. This study aims to determine the effect of teacher professional competence on students' learning motivation in the subjects of Islamic religious education and morals in class XII IPS at SMA Negeri 3 Kota Sukabumi. The research model used in this research is a survey model with a quantitative approach. The sampling technique uses Sample Random Sampling. The instrument used is a Likert scale with 5 possible answers (SS = Strongly agree, S = Agree, RG = Undecided, TS = Disagree, STS = Strongly disagree). With the number of questions 15 variables X and 15 variables Y. Based on the results of the regression analysis, it was found that the regression coefficient value was 0.489, this value indicated a positive value. In addition, it is supported by a tcount > ttable (2.407 > 2.069) at a significance level of 0.05 (5%), meaning that Teacher Professional Competence has a positive and significant influence on the Learning Motivation of students at SMA Negeri 3 Kota Sukabumi.